Efficacy and Safety of Indacaterol/Glycopyrronium (IND/GLY) Versus Salmeterol/Fluticasone in Chinese Patients with Moderate-to-Severe Chronic Obstructive Pulmonary Disease: The Chinese Cohort from the LANTERN Study. (1st November 2016) - Zhong, Nanshan; Wang, Changzheng; Zhou, Xiangdong; Zhang, Nuofu; Humphries, Michael; Wang, Linda; Patalano, Francesco; Banerji, Donald
ABSTRACT: Inhaled indacaterol/glycopyrronium fixed-dose combination (IND/GLY) is approved in over 80 countries, including the EU, Japan, Australia and Switzerland and the US. The LANTERN study evaluated the efficacy of IND/GLY compared with inhaled long-acting β2 -agonist (LABA)/inhaled corticosteroid (ICS) or salmeterol/fluticasone (SFC) in patients with moderate-to-severe COPD with a history of ≤1 exacerbation in the previous year. Here we present the efficacy and safety of IND/GLY versus SFC in the Chinese cohort from the LANTERN study. LANTERN was a 26-week, multicenter, randomized, double-blind, double-dummy, parallel-group study conducted in patients with moderate-to-severe COPD with a history of ≤1 exacerbation in the previous year. The patients were randomized (1:1) to once-daily IND/GLY (110/50 μg) or twice-daily SFC (50/500 μg). The primary endpoint was non-inferiority of IND/GLY versus SFC in terms of trough FEV1 . Of the total 744 patients randomized in the LANTERN study, 598 (80.4%) were from Mainland China and randomized to IND/GLY (n = 298) or SFC (n = 300), and 553 (92.5%) completed the study. IND/GLY showed superiority over SFC with a statistically significant and clinically meaningful improvement in trough FEV1, FEV1 AUC0–4h, peak FEV1 and trough forced vital capacity (FVC) change from the baseline. Annualized rate of moderate or severe COPD exacerbations was significantly lower (43%) with IND/GLY compared with SFC (rate ratio: 0.57, p = 0.015). Overall, adverse events were lower for IND/GLY (34.6%) versus SFC (43.1%). IND/GLY was superior in achieving bronchodilation versus SFC in a Chinese subgroup of patients from this study. Clinicaltrials.gov identifier : NCT01709903